2021
DOI: 10.1039/d0fo03185b
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid ameliorates Klebsiella pneumoniae-induced pneumonia in immunosuppressed mice via inhibiting the activation of NLRP3 inflammasomes

Abstract: Chlorogenic acid (CGA) possesses a wide variety of bioactive properties, such as antioxidation, anti-inflammation and anti-bacteria. This study was aimed at exploring the effects of CGA of anti-inflammation and anti-bacteria...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Among them, there were 377 intersecting targets. Taking the therapeutic effect of active ingredients on phlegm, cough and asthma as the primary reference standard and the position of active ingredients in drugs as the secondary standard, literature research was carried out, and finally six main quality control index components of MXZ syrup were selected, including ephedrine (Wang et al, 2022; Wei et al, 2019), chlorogenic acid (Li et al, 2021; Zeng et al, 2021), amygdalin (Tang et al, 2019; Wang et al, 2019), harpagoside (Zhang et al, 2017) and forsythin (Coon et al, 2014) and forsythoside A (Zheng et al, 2019). According to the order of degree value, SRC, HSP90AA1, PTPN11, CTNNB1, EP300, ESR1, F2, PIK3R1, ITGB3 and CREBBP were considered as the top 10 core targets.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, there were 377 intersecting targets. Taking the therapeutic effect of active ingredients on phlegm, cough and asthma as the primary reference standard and the position of active ingredients in drugs as the secondary standard, literature research was carried out, and finally six main quality control index components of MXZ syrup were selected, including ephedrine (Wang et al, 2022; Wei et al, 2019), chlorogenic acid (Li et al, 2021; Zeng et al, 2021), amygdalin (Tang et al, 2019; Wang et al, 2019), harpagoside (Zhang et al, 2017) and forsythin (Coon et al, 2014) and forsythoside A (Zheng et al, 2019). According to the order of degree value, SRC, HSP90AA1, PTPN11, CTNNB1, EP300, ESR1, F2, PIK3R1, ITGB3 and CREBBP were considered as the top 10 core targets.…”
Section: Resultsmentioning
confidence: 99%
“…75 CA has been reported to inhibit Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) activation, thus inhibiting the production of NO and IL-1β in the LPS-induced RAW 264.7 murine macrophages. 76,77 Liu et al found that chlorogenic acid, rosmarinic acid and isofraxidin extracted from Sarcandra glabra could decrease the secretion of NO, IL-6, and TNF-α in LPS-treated RAW264.7 macrophage cells. 78 Fang et al found that alginate-derived guluronate oligosaccharide significantly suppressed inducible nitric oxide synthase (iNOS) expression, NO release and TNF-α secretion in LPS-induced RAW264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that two active substances obtained from flowers of Lonicera japonica , 7-acetyl-8,9-dihydroxy thymol, and 7,8-dihydroxy-9-buyryl thymol play antibacterial effects on Staphylococcus aureus , Escherichia coli , Micrococcus luteus , and Bacillus cereus [ 26 , 27 ]. Chrysanthemum morifolium extract represses the growth of different intestinal pathogenic bacteria, such as Enterobacter , Enterococcus , Clostridium , and Bacteroides [ 28 ].…”
Section: Discussionmentioning
confidence: 99%